antistih (anti-verse), Church Slavonic language, Church Slavonic graphics, Church Slavonic orthography, homonymy, book correction, apostrof (apostrophe), diacritics - Dmitry V. Rudnev; Tatiana S. Sadova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The article deals with various metaphorical models of the state structure of Russia from the Ancient Russian era to the 20 th century and linguistic means of their representation in official speech. It is assumed that the primary metaphor of the medieval state as a family state, reflected in a special “familiar” type of official communication, is focused on oral colloquial speech. The sovereign was presented as the parent of his citizens, the dependence of one prince on another was defined in terms of kinship, the reference of people towards those in authority was expressed using speech formulas with the modality of demand, disparagement, exhortation, submission, and the like. The state-as-mechanism metaphor comes to replace the family metaphor in the era of Peter the Great’s reign. Decrease in emotionality and elimination of familiarity from official speech, as well as the introduction of document formatting standards have been revealed. The logical continuation of this metaphor is the “court” model of the state structure in Russia since the era of Catherine the Great, when intrastate communication featured compliance with the rules of etiquette and decency of court interaction, which tended to overcame the rigour and accuracy in expressing the purpose of communication. Further periods in the history of Russian business speech appear as combinations of ways of expressing these three basic metaphorical models.